The Relationship Between Academic Anxiety and Academic Procrastination in Students of the Faculty of Psychology and Education, University of Muhammadiyah Sidoarjo: Hubungan Antara Kecemasan Akademik dengan Prokrastinasi Akademik pada Mahasiswa Fakultas Psikologi dan Ilmu Pendidikan Universitas Muhammadiyah Sidoarjo - Sari, Mega Puspita; Hazim, Hazim (Universitas Muhammadiyah Sidoarjo, 2023)
Students often delay completing coursework, this is called academic procrastination. Academic procrastination occurs due to personal factors such as fear, failure, anxiety and depression. The purpose of this study was to determine the relationship between academic anxiety and academic procrastination in students. The population of this research is active students of the faculty of psychology and education, Muhammadiyah University of Sidoarjo, totaling 2200 students with a sample of 241 students taken by simple random sampling technique. Data collection techniques using a Likert scale and data analysis techniques using Pearson product moment correlation. The results of data analysis obtained rxy = 0.457 with sig 0.000 <0.05. The highest hypothesis is accepted, which means that there is a positive relationship between academic anxiety and academic procrastination in students.